Level of Knowledge about Hypertension in Cilayung Village District Jatinangor, Sumedang - Qisthi, Dian; Wiwaha, Guswan; Martakusumah, Abdul Hadi; Setiawati, Elsa Pudji (Althea Medical Journal, 2015)
Â Â Background: Hypertension known as a silent killer because it is often asymptomatic and causes target organ damage. Prevention of hypertension and its complications are pharmacological and non-pharmacological therapy, making holistic knowledge of hypertension is paramount to establish good behavior. This is needed by hypertensive and non-hypertensive individuals. Therefore, the study was conducted to identify any knowledge level differences between hypertensive and non-hypertensive groups.Â Methods: Respondents were 116 Cilayung residents equally divided in hypertensive and non-hypertensive groups. Respondentâs blood pressure was measured and they completed questionnaires during October 2012. This is an observational analytic cross-sectional study with chi-square test.Results: The respondentsâ characteristics in both groups dominated by females, aged 50-59 years, housewives, with elementary school background. Most respondents in both groups had sufficient knowledge about hypertension in general, but for knowledge about risk factors, treatment, and complications were still not enough. The result of the chi-square test was not significant with P=0.676. It was due to distributed health promotion and non-matched respondentsâage.Conclusion: There is no difference in level of knowledge about hypertension between both groups in Cilayung.Keywords: Differences, hypertension, level of knowledgeÂ DOI: 10.15850/amj.v2n1.449Â